Exploring professionals’ understanding, interpretation and implementation of the ‘appropriate medical treatment test’ in the 2007 amendment of the Mental Health Act 1983 - Perry, Benjamin I. (BJPsych Open, 2017)
BACKGROUND: The appropriate medical treatment test (ATT), included in the Mental Health Act (MHA) (1983, as amended 2007), aims to ensure that detention only occurs when treatment with the purpose of alleviating a mental disorder is available. AIMS: As part of the Assessing the Impact of the Mental Health Act (AMEND) project, this qualitative study aimed to assess professionals’ understanding of the ATT, and its impact on clinical practice. METHOD: Forty-one professionals from a variety of mental health subspecialties were interviewed. Interviews were coded related to project aims, and themes were generated in an inductive process. RESULTS: We found that clinicians are often wholly relied upon for the ATT. Considered treatment varied depending on the patient’s age rather than diagnosis. The ATT has had little impact on clinical practice. CONCLUSIONS: Our findings suggest the need to review training and support for professionals involved in MHA assessments, with better-defined roles. This may enable professionals to implement the ATT as its designers intended. DECLARATION OF INTEREST: None. COPYRIGHT AND USAGE: © The Royal College of Psychiatrists 2017. This is an open access article distributed under the terms of the Creative Commons Non-Commercial, No Derivatives (CC BY-NC-ND) license.